GEOGRAPHICAL DISTRIBUTION AND STATUS OF SCADS POPULATION IN THE WATERS OF THE SOUTHERN PART OF THE SUNDA SHELF - Suherman Banon Atmaja; Duto Nugroho (Indonesian Fisheries Research Journal, 2005)
The scads population have long been exploited in ldonesia Exploitation to the offshore water started when purse seine was introdused in 1970. The exploitation extends eastwards to the Macassar Strait and nonhwards to the southern part of the south china sea.